Mast cells and factor XIIIa+ dendrocytes in actinic cheilitis and lip squamous cell carcinoma - Flores, Isadora Luana; Arruda, José Alcides Almeida DE; Abrantes, Thamiris de Castro; Gamba, Thiago de Oliveira; ABRAHÃO, Aline Correa; Anbinder, Ana Lia [UNESP]; Ribeiro, Jaqueline Lemes [UNESP]; Vasconcelos, Ana Carolina Uchoa; Andrade, Bruno Augusto Benevenuto de; Aguiar, Maria Cassia Ferreira de; Gomes, Ana Paula Neutzling; Abreu, Lucas Guimarães; et al. (My University, 2024)
There is an interaction between dendrocytes and mast cells in the skin. However, in elastosis-related diseases such as actinic cheilitis (AC) and lower lip squamous cell carcinoma (LLSCC), this interaction remains unknown. We investigated the presence of intact and degranulated mast cells in AC and LLSCC. Associations of mast cells with factor XIIIa+ dendrocytes and inflammatory infiltrate were assessed. Forty cases of AC (20 with low-grade and 20 with high-grade epithelial dysplasia), 50 cases of LLSCC, and 10 cases of normal oral mucosa were evaluated. Toluidine blue staining was performed to identify mast cells, and mast cell densities were calculated in the inflammatory infiltrate. Factor XIIIa+ dendrocytes were immunohistochemically quantified. The highest ratio of intact/degranulated mast cells density was detected in LLSCC (5.9 cells/mm2), followed by AC with high-grade epithelial dysplasia (4.8 cells/mm2). Statistically significant differences were found in the density of intact mast cells compared to degranulated mast cells in AC with low-grade epithelial dysplasia (p<0.001), AC with high-grade epithelial dysplasia (p=0.005), and LLSCC (p<0.001). A positive correlation between degranulated mast cells and total inflammatory infiltrate (p=0.03) was observed in the LLSCC group. The expression of factor XIIIa+ dendrocytes was highest in AC with low-grade epithelial dysplasia (16.5 cells/mm2). The link between mast cell density, factor XIIIa+ dendrocytes, and inflammatory infiltrate indicates a potential crosstalk in lip carcinogenesis.
Keywords: Carcinoma, Squamous Cell; Cell Degranulation; Factor XIIIa; Mast Cells